Intensive culture social theory, religion and contemporary capitalism - Lash, Scott; SAGE Knowledge (Online service). (Los Angeles, Calif. Sage, 2010)
"Contemporary culture, today's capitalism, [and] our global information society is ever-expanding [and] ever more extensive. And yet we seem to be experiencing a parallel phenomenon which can only be characterized as intensive. This book is dedicated to the study of such intensive culture. While extensive culture is a culture of the same: a culture of fixed equivalence; intensive culture is a culture of difference, of in-equivalence - the singular. Intensities generate what we encounter. They are virtuals or possibilities, always in process and always in movement. Lash carefully defines and distinguishes the intensive from the extensive tracking this change through key areas of social life including: Sociology, Religion, Philosophy, Language, Politics, [and] Communication."-Provided by publisher.
Introduction -- Intensive sociology: Georg Simmel's Vitalism -- Intensive philosophy: Leibniz and the ontology of difference -- Intensive language: Benjamin, God and the name -- Intensive capitalism: Marxist ontology -- Intensive politics: power after hegemony -- Intensive religion: Emile Durkheim's elementary forms -- Information theology: Philip K. Dick's will to knowledge -- Conclusions.
Includes bibliographical references (p. [227]-234) and index.
Keywords: Culture; Culture and globalization; Religion and culture; Capitalism; Civilization, Modern; Electronic books